Gestos emblemáticos produzidos por duas crianças com Síndrome de Down na terapia fonoaudiológica - Melo, Ediclécia Sousa de (2017)
Down syndrome is a genetic disorder caused by the presence of three 21 chromosomes in all or part of cells, resulting in a specific facial appearance, as well as muscular hypotonia, hearing and visual problems, and, in general, individuals with Down syndrome present delays in their development. The literature of the area points out that the process of language acquisition in these children is considered slow, and that the gestural productions are more privileged than the vocal productions. On the other hand, more recent language acquisition studies point to a linguistic multimodality, showing that linguistic productions are favored through speech-language intervention. In addition, it is clear that emblems (cultural gestures, such as pointing, waving, etc.) are privileged in communicative exchanges. Therefore, the objective of this work is to analyze the multimodal productions (emblems and vocal production) of two children with DS in clinical context.These participants are two siblings, whose initial ages are 36 months, in the case of one child (C1), and 60 months, as for the other sibling (C2). The data were filmed at the Clinical School of Speech Therapy at a public university in Paraiba. The collection was done by means of recording images, with duration of 30 minutes (estimated time of speech therapy), fortnightly, and consented by the supervisors, therapists and those responsible for the children. The data were then recorded on DVD media and transcribed in ELAN (Eudico Linguistic Annotator). In the mentioned software, we observed and transcribed the multimodal productions (gestures, vocal productions and look) by the children and therapists. In view of the analyses made, it is observed that the emblems are gestures widely produced by these two children, especially the gesture of pointing, executed with referential purposes. It is quantitatively observed that each child has a specific emblematic production, since C1 has fewer emblems and a varied vocal production, whereas C2 produces more emblems (with emphasis on deictic gestures), there is an absence of vocal production and greater insertion in scenes of Joint Attention. At the end of the study, it is possible to verify that the emblems are gestures used by both children and therapists in a multimodal way. In addition, it was observed that the clinical context is a space that favors the interaction between the subjects. Each child participates in the communicative exchanges with the multimodal resources that are available to them, constituting themselves as interactive subjects in the scenes of Joint Attention. Keywords: Down syndrome; Language acquisition; Multimodality; Emblems.